Maximizing the Extraction of Albumin from Common Carp (Cyprinus carpio Linnaeus, 1758) with Variations in Temperature and HCl Solvent Concentrations - nurfaidah, Nurfaidah (Journal of Agritechnology and Food Processing, 2025)
Albumin is a globular protein that plays a crucial role in various biological functions, including regulating blood osmotic pressure and transporting small molecules in the body. With the growing demand and high production costs of albumin derived from human plasma, exploring alternative sources such as fish is important. This study aims to optimize the extraction of albumin from common carp (Cyprinus carpio) using hydrochloric acid (HCl) solvent at different concentrations and heating temperatures. The fish flesh, after being finely ground, was mixed with HCl solvent and heated in a water bath for 30 minutes. The results showed that albumin yields varied between 0.94% and 3.55% (w/w). The highest yield was achieved with 0.1 M HCl at 35°C, reaching 3.55%, while the lowest yield was obtained with 0.2 M HCl at 27°C, which was 0.94%. Moderate temperatures and the appropriate HCl concentration allow effective protein denaturation without excessive damage, making it the optimal extraction method. These findings indicate that extraction with 0.1 M HCl at 35°C is the best condition for maximizing albumin yield from common carp. The study also provides a basis for further exploration of alternative extraction methods and environmentally friendly solvents, as well as an economic feasibility assessment at the industrial scale.